Brain Network Analysis of EEG Recordings Can Be Used to Assess Cognitive Function in Teenagers With 15q13.3 Microdeletion Syndrome - Stern, Tehila; Crutcher, Emeline H.; McCarthy, John M.; Ali, May A.; Issachar, Gil; Geva, Amir B.; Peremen, Ziv; Schaaf, Christian P. (Frontiers in Neuroscience, 2021)
15q13.3 microdeletion syndrome causes a spectrum of cognitive disorders, including intellectual disability and autism. We assessed the ability of the EEG analysis algorithm Brain Network Analysis (BNA) to measure cognitive function in 15q13.3 deletion patients and to differentiate between patient and control groups. EEG data were collected from ten individuals with 15q13.3 microdeletion syndrome (14–18 years of age), as well as thirty age-matched healthy controls, as the subjects responded to Auditory Oddball (AOB) and Go/NoGo cognitive tasks. It was determined that BNA can be used to evaluate cognitive function in 15q13.3 microdeletion patients. This analysis also significantly differentiates between patient and control groups using 5 scores, all of which are BNA-Based produced from ERP peaks related to late cortical components that represent higher cognitive functions of attention allocation and response inhibition (P < 0.05).